Pedaling technique and energy cost in cycling - Leirdal, S.; Ettema, G. (Medicine & Science in Sports & Exercise, 2011)
Purpose: Because cycling is an extreme endurance sport, energy saving and therefore efficiency is of importance for performance. It is generally believed that gross efficiency (GE) is affected by pedaling technique. A measurement of pedaling technique has traditionally been done using force effectiveness ratio (FE; ratio of effective force and total force). The aim of the present study was to investigate the relationship among GE, FE, and a new technique parameter, dead center (DC) size in competitive cyclists.